Contextual FPB Fun Day Improves Numeracy Literacy and Conceptual Understanding: FPB Fun Day Kontekstual Meningkatkan Literasi Numerasi dan Pemahaman Konsep - Salsabila, Eka Aprilia; Habibah, Sulhatul; Rahmawati, Zuli Dwi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Mathematics learning in elementary schools plays a crucial role in developing logical thinking and problem-solving skills; however, it is often dominated by procedural exercises. Specific Background In the context of learning the greatest common factor (FPB) in class V MI Ma’arif NU Sukolilo, teaching practices remain focused on lectures and written tasks, limiting students’ conceptual understanding and numeracy literacy. Knowledge Gap This condition indicates a gap between concept-oriented mathematics learning and the conventional instructional practices that do not sufficiently engage students in contextual and meaningful experiences. Aims This study aims to describe the implementation of the FPB Fun Day co-curricular program and analyze its role in improving numeracy skills, FPB conceptual understanding, and numeracy literacy. Results Using a descriptive qualitative approach, the findings reveal that FPB Fun Day is implemented through contextual activities such as distributing objects evenly, increasing student participation, conceptual comprehension, and the ability to interpret and communicate mathematical problems. Students with higher abilities tend to apply conventional strategies, while those with difficulties benefit more from contextual approaches. Novelty The study introduces a co-curricular, experience-based learning model integrating FPB concepts with numeracy literacy through real-life activities beyond classroom routines. Implications The findings suggest that contextual and activity-based learning can serve as an alternative strategy for strengthening conceptual understanding and numeracy literacy, supported by teacher creativity, student engagement, and institutional support despite challenges in time management and varying student abilities. Highlights • Contextual activities using real objects support deeper mathematical reasoning• Learners with lower abilities gain clearer understanding through visual practice• Collaborative tasks promote active participation and logical problem solving Keywords FPB Fun Day; Mathematics Learning; Numeracy Literacy; Conceptual Understanding; Contextual Learning